1998
DOI: 10.1080/014608698265528
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating the Transition of Adolescents With Chronic Conditions From Pediatric to Adult Health Care and Community Settings

Abstract: This article provides an overview of the health care issues and concerns of adolescents with special health care needs and disabilities who are in transition from pediatric to adult health care settings. Adolescents and their families face numerous challenges in accessing adult health care providers who can give adequate primary and specialized health care services to this growing population of youth. Navigating the myriad new and unfamiliar adult services available can be overwhelming for adolescents, their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 18 publications
1
30
0
2
Order By: Relevance
“…These revolve around the achievement of autonomy and independence in health-related decision-making and self-care. Variations of the same theme include self-sufficiency, self-management, mastery, competence, and shared-care (AAP, 2013;Betz, 1998aBetz, , 1998bBetz, 2000;Fleming et al, 2002;Hergenroeder, 2002;Higgins & Tong, 2003;Kelly et al, 2002;Luther, 2001;Okumura et al, 2014;Swallow et al, 2013;Tong & Kools, 2004;Towns & Bell, 2010)). Other noted consequences include normalization, reassignment of roles and responsibilities, and reintegration into a new system of adult health (Kelly et al, 2002).…”
Section: Antecedents and Consequencesmentioning
confidence: 96%
See 2 more Smart Citations
“…These revolve around the achievement of autonomy and independence in health-related decision-making and self-care. Variations of the same theme include self-sufficiency, self-management, mastery, competence, and shared-care (AAP, 2013;Betz, 1998aBetz, , 1998bBetz, 2000;Fleming et al, 2002;Hergenroeder, 2002;Higgins & Tong, 2003;Kelly et al, 2002;Luther, 2001;Okumura et al, 2014;Swallow et al, 2013;Tong & Kools, 2004;Towns & Bell, 2010)). Other noted consequences include normalization, reassignment of roles and responsibilities, and reintegration into a new system of adult health (Kelly et al, 2002).…”
Section: Antecedents and Consequencesmentioning
confidence: 96%
“…There is a critical need to prepare nurses at all levels, especially those at the advanced practice/nurse practitioner roles, to provide compassionate, developmentally-appropriate care to adolescents with chronic conditions (Betz, 1998b;Betz & Redcay, 2005;Hauser & Dorn, 1999;Higgins & Tong, 2003). A sensitive discussion on transitioning to AHC must be initiated in a timely manner while their health status is stable.…”
Section: Educationmentioning
confidence: 98%
See 1 more Smart Citation
“…Other literature indicates that an obstacle to a successful transition may occur if the paediatric caregiver has strong emotional bonds with the family and the patient, or does not trust the adult caregiver. 23,24 In addition, Rosen 7 has indicated that the paediatric doctor's perceptions are unintentionally communicated to patients and families and that this may compound their resistance to transition efforts.…”
Section: Paediatric Health Carementioning
confidence: 96%
“…F or more than a decade, child health advocates have recognized that adolescents with chronic health conditions require a well-planned and coordinated transition between pediatric and adult services (Alberta Child and Youth Initiative, 2007;American Academy of Pediatrics, 2002;Betz, 1998Betz, , 2004Blum, 1995;Blum et al, 1993;Canadian Paediatric Society, 2007;McDonagh, 2007). However, most of the information regarding transition is in the form of policy recommendations or is anecdotal, with scant literature describing detailed transition services for adolescents with special healthcare needs (Betz & Redcay, 2003).…”
mentioning
confidence: 98%